Effort Increasing Math Learning Results Through Implementation Of Classroom Class Methods III In SDN 01 Merigi Lesson Year 2015/2016 - Esmiyati Esmiyati (JURIDIKDAS, 2018)
Classroom action research "The Use of Mute Game Methods to improve the learning outcomes of third grade mathematics students at Elementary School 01 Merigi (about the multiplication of crop numbers). This research is in the background by observation of mathematics learning of students who consider mathematics is a difficult lesson. From this assumption most students are reluctant to learn, the impact of students' understanding of mathematics is still felt weak. The purpose of this study is to determine whether through the method of mute game can improve student learning outcomes in the subject of multiplication number of counting in class III in Elementary School 01 Merigi Kepahiang Regency, Bengkulu Province. The research was conducted using a classroom action research approach. This study consists of two cycles, taking the Competency Standard: recognizing and using the concept of counting in problem solving. Based on the results of research can be obtained the average formative value of students from cycle I with an average value of 59.5, cycle II with an average value of 78, while the average value of group I cycle with a value of 5.9 and cycle II with the value 7.8. Data obtained by researcher from research subjects of third grade students at Elementary School 01 Merigi and questionnaire and interview. Based on the results of research and discussion can be concluded that the use of mute game method can improve student learning outcomes in the subject of multiplication number of counts.